What is Scientific Reality? - Hossain, Mohammad Shahadat (Journal of Critical Realism in Socio-Economics (JOCRISE), 2025)
Scientific progress in AI, Big Data, and FINTECH has revolutionized human life but also intensified inequality, surveillance, and ecological crises. This paper argues that such contradictions arise from modern science’s separation of morality from materiality. It advances the Law of Unity of Knowledge, integrating ethical consciousness (“being”) with empirical reality (“becoming”) through circular causation. The framework, rooted in insights from Einstein, Hawking, Whitehead, and Imam Ghazali, culminates in a Wellbeing Function that links sustainability to moral-material complementarity. Applications include ethical AI in healthcare and Qur’ānic principles of trusteeship in agriculture, redefining scientific reality as holistic, ethical, and transformative